Trends in Racial/Ethnic Representation Among US Medical Students - Lett, Elle (JAMA Netw Open, 2019)
IMPORTANCE: With increasing efforts to create a diverse physician workforce that is reflective of the demographic characteristics of the US population, it remains unclear whether progress has been made since 2009, when the Liaison Committee on Medical Education set forth new diversity accreditation guidelines. OBJECTIVE: To examine demographic trends of medical school applicants and matriculants relative to the overall age-adjusted US population. DESIGN, SETTING, AND PARTICIPANTS: Repeated cross-sectional study of Association of American Medical Colleges data on self-reported race/ethnicity and sex of medical school applicants and matriculants compared with population distribution of the medical school–aged population (20-34 years). Data from US allopathic medical school applicants and matriculants from 2002 to 2017 were analyzed. MAIN OUTCOMES AND MEASURES: Trends were measured using the representation quotient, the ratio of the proportion of a racial/ethnic group in the medical student body to the general age-matched US population. Linear regression estimates were used to evaluate the trend over time for Asian, black, white, Hispanic, American Indian or Alaska Native (AIAN), and Native Hawaiian or Other Pacific Islander medical school matriculants by sex. RESULTS: The number of medical school applicants increased 53%, from 33 625 to 51 658, and the number of matriculants increased 29.3%, from 16 488 to 21 326, between 2002 and 2017. During that time, proportions of black, Hispanic, Asian, and Native Hawaiian or Other Pacific Islander male and female individuals aged 20 to 34 years in the United States increased, while proportions of white male and female individuals decreased and proportions of AIAN male and female individuals were stable. From 2002 to 2017, black, Hispanic, and AIAN applicants and matriculants of both sexes were underrepresented, with a significant trend toward decreased representation for black female applicants from 2002 to 2012 (representation quotient slope, −0.011; 95% CI, −0.015 to −0.007; P < .001). CONCLUSIONS AND RELEVANCE: Black, Hispanic, and AIAN students remain underrepresented among medical school matriculants compared with the US population. This underrepresentation has not changed significantly since the institution of the Liaison Committee of Medical Education diversity accreditation guidelines in 2009. This study’s findings suggest a need for both the development and the evaluation of more robust policies and programs to create a physician workforce that is demographically representative of the US population.